1982
DOI: 10.1037/0022-3514.43.5.901
|View full text |Cite
|
Sign up to set email alerts
|

Influence of affect on cognitive social learning person variables.

Abstract: This study examined the influence of feeling states on person variables viewed as central mediators of self-regulation and performance within a cognitive social learning formulation of personality. Subjects generated either positive, neutral, or negative affective states through their own ideation and were then exposed to success or failure outcomes over a series of trials. Positive affect resulted in increased expectations, higher estimates of past successes, and more favorable global selftevaluations. Conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(160 citation statements)
references
References 28 publications
6
141
0
3
Order By: Relevance
“…For example, students induced into experiencing a positive mood thereafter describe themselves in more positive terms (Sarason, Potter, & Sarason, 1986), assess their task performance as superior (Barsade, 2002), report more favorable global self-evaluations, and recall more positive experiences and successes from their past (M. S. Clark & Waddell, 1983;Wright & Mischel, 1982). Happy moods also appear to increase feelings of self-efficacy.…”
Section: Self-perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, students induced into experiencing a positive mood thereafter describe themselves in more positive terms (Sarason, Potter, & Sarason, 1986), assess their task performance as superior (Barsade, 2002), report more favorable global self-evaluations, and recall more positive experiences and successes from their past (M. S. Clark & Waddell, 1983;Wright & Mischel, 1982). Happy moods also appear to increase feelings of self-efficacy.…”
Section: Self-perceptionsmentioning
confidence: 99%
“…Those put in a good mood report higher self-efficacy (Baron, 1990;Samson & Rachman, 1989;Schuettler & Kiviniemi, in press) and set higher goals for themselves (Baron, 1990;Hom & Arbuckle, 1988). Induced positive moods also lead people to expect more success on laboratory tasks (Brown, 1984;Wright & Mischel, 1982). Finally, positive mood leads individuals to attribute their successes to stable factors within themselves (Brown, 1984).…”
Section: Self-perceptionsmentioning
confidence: 99%
“…For example, when compared with a neutral affect group, people induced to experience positive affect set higher goals for themselves (Baron, 1990;Hom & Arbuckle, 1988), persist at a difficult task longer (Sarason, Potter, & Sarason, 1986), evaluate themselves more positively (Sarason et al, 1986), and rate their performance as stronger (Barsade, 2002;Wright & Mischel, 1982). On laboratory tasks, people experiencing positive emotions are also more optimistic about the outcomes (Brown, 1984;Wright & Mischel, 1982). It is interesting that such positive evaluations are not merely unjustified impressions; people in a happy mood often perform better than those in a sad mood (Hom & Arbuckle, 1988; see below for contradictory findings regarding performance on complex mental tasks).…”
Section: Experimental Evidence: Does Happiness Lead To Success In Thementioning
confidence: 99%
“…Recently, it has been demonstrated that depressed mood also influences people's effort mobilization in terms of their cardiovascular response during execution of various mental tasks Gendolla 2007, 2008). These findings have been interpreted as a mood-congruent informational impact on individual's task demand appraisals (see e.g., Gendolla et al 2001;Kavanagh and Bower 1985;Wright and Mischel 1982), which in turn determine effort mobilization. However, these recent studies cannot provide clear evidence that an informational mood impact is responsible for the effects of depressed mood on cardiovascular reactivity.…”
Section: Introductionmentioning
confidence: 99%